Cannabis use in people with Multiple Sclerosis: the highway to lower disability? - Kindred, John Harvey, author; Rudroff, Thorsten, advisor; Kalliokoski, Kari K., committee member; Kraft, Susan L., committee member; Tracy, Brian L., committee member (Colorado State University. Libraries, 2017)
The following dissertation describes a series of investigations designed to identify possible effects of cannabis use in people with Multiple Sclerosis. The specific aims of the three projects were: 1) to determine the proportion of people with Parkinson's Disease and Multiple Sclerosis currently using cannabis and collect self-reported measures of disability, to include physical function, balance, and fatigue; 2) to determine if people with Multiple Sclerosis using cannabis perform better on functional tasks compared to individuals who are not using cannabis; 3) to determine if resting brain glucose uptake is altered in people with Multiple Sclerosis using cannabis compared to people not using cannabis. In Project 1 we found that a large portion of people with Parkinson's disease and Multiple Sclerosis responding to our survey are currently using cannabis. These individuals are also reporting lower levels of neurological disability, especially within the realms of mood, memory, and fatigue. A large majority of participants also reported reducing the amount of prescription medications since starting cannabis use. In project 2 we compared objective and subjective measurements of neurological disability between current cannabis users and data taken from a previous investigation investigating predictors/correlates of physical activity in people with Multiple Sclerosis. When we compared the users versus the non-users we found that users reported higher levels of fatigue as assessed by the fatigue severity scale questionnaire. We also found that people with Multiple Sclerosis using cannabis performed worse on the Paced Auditory Serial Addition Test, which is a measure of cognitive function. Project 3 utilized Positron Emission Tomography to measure brain glucose uptake with the glucose analog tracer [18F]-Fluorodeoxyglucose. Higher levels of glucose uptake were beneficially correlated with disability status, fatigue, and pain in our sample. These findings agree with previous studies and indicated that brain glucose uptake can be used as a biomarker in people with multiple sclerosis. When our sample was dichotomized into current cannabis users and non-users measures of disability were similar, except that cannabis users performed more poorly during cognitive function testing. Even though most measures of disability were similar between the groups, cannabis users were found to have greater glucose uptake throughout areas of the frontal and temporal lobes. This suggests that cannabis may provide beneficial effects in maintaining nervous system glucose uptake but may also be accompanied by negative effects on cognition in people with multiple sclerosis.